The Image: Constraint or Advantage for Film Subtitles? - Sinu Raluca (RIELMA, 2013)
This paper discusses the role of one of the main components of audiovisual productions, i.e. the image, in the translation of films. Its aim is to highlight the influence of the image on the way film dialogue is translated, in an attempt to ascertain whether image acts as a constraint or as an advantage for the quality of the subtitles. The paper starts by examining the polysemiotic composition of the audiovisual material and the main features of subtitling as a form of constrained translation. Then it investigates two of the levels at which image and subtitles interact: the image as situational context and the linguistically relevant image.
Keywords: audiovisual text; subtitling; polysemiotic composition; image